(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
The s.c. “Sandalbinder Venus” has to be considered one of the most widespread and popular sculptural types from Hellenistic and Roman-era, as testified by hundreds of replicas. Imitations and adaptations inspired by this ancient model have been produced in modern times since the Renaissance. Between the end of the XIX and the beginning of the XX century, the diffusion of a large number of copies of a statuette discovered in Herculaneum in 1757 marks a renewed success of the type. This development can be traced back to the activity of some Neapolitan art foundries – Chiurazzi, De Angelis and Sommer above all – operating in the reproduction of original archaeological works from the Vesuvian area. The analysis of this case study can contribute to understand the evolution of the «industrial art on the path of classicism», considering implications related to the reproduction, forgery and antiquities collecting, but also to the reception of ancient art within modern visual culture.